Emotional well-being years post-treatment for breast cancer: prospective, multi-ethnic, and population-based analysis - Janz, Nancy K. (2013)
PURPOSE: This study investigated factors associated with declines in emotional well-being (EWB) over time in breast cancer survivors. METHODS: Women with breast cancer (Stages I-III) residing in Los Angeles, CA or Detroit, MI and reported to the Surveillance, Epidemiology, and End Results registries between June 2005-February 2007 completed surveys at 9 months and 4 years after diagnosis. EWB was measured by the Functional Assessment of Cancer Treatment-Breast. Using a stress coping framework, logistic regression models assessed associations between personal, social, and clinical correlates, appraisal (e.g., worry about recurrence) and coping factors (e.g., emotional support) to EWB declines. RESULTS: Among eligible women who completed primary breast cancer treatment, 772 completed both surveys and 192 (24.9%) experienced EWB declines over time. Women with past or current depression were more likely to report EWB decline (p<.01). Survivors who perceived they did not receive enough information about risk of breast cancer recurrence during primary treatment were more likely to have EWB decline (OR 0.53, 95% CI 0.32-0.87). Greater perceived likelihood of recurrence (OR 1.95, 95% CI 1.01-5.29) and increased worry about recurrence (OR 1.38, 95% CI 1.10-1.72) were associated with EWB decline. Higher spirituality beliefs and practices were associated with EWB decline. CONCLUSIONS: A considerable number of breast cancer patients report emotional well-being declines over time. Early identification of women who are vulnerable, such as women with past depression, is crucial to improve quality of care. Women would benefit from education about cancer recurrence and tailored strategies to manage worry about recurrence over time. IMPLICATION FOR CANCER SURVIVORS: Understanding actual risk of recurrence and managing worry about recurrence is important for cancer survivors. Emotional concerns are common for individuals with cancer so survivors should feel free to reach out and discuss such concerns with providers well into the survivorship period.